Music Composition “Entik” | Komposisi Musik “Entik” - I Wayan Arya Bisma; I Wayan Suharta (GHURNITA: Jurnal Seni Karawitan, 2022)
Root growth always develops to form new branches so that it forms a very unique physique with irregular links that make the physical form of the root look complicated. This phenomenon stimulates the author's mind to transfer it into the form of a musical composition art form entitled Entik. This phenomenon is interpreted by processing the range of tones, interweaving patterns and interweaving between instruments, developing instrument functions, rhythms, tempos and dynamics that are processed in a minimalist manner, which are presented using the medium of the gamelan semarandhana. The creation of this work was realized using the creation method Panca Sthiti Ngawi Sani, which consists of five stages of creation, namely: Ngawirasa, Ngawack, Ngarancana, Ngewangun and Ngebah.   Keywords: root, entik, karawitan